Effect of Distribution Channel Strategies on the Performance of Banks - Dickson Ben Uche; Jane Nwakaego Anene; Emezue Leonard Nnabugwu (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
Effective distribution channel strategy selection, application, and management does not only help to meet the shopping needs and habits of the target customers efficiently under the cost restraints of the seller; they must also lessen the drawbacks caused by distribution channel conflicts such as double downgrading. This study evaluated the effect of distribution channel strategies on the performance of commercial banks in Nigeria. The objective of the study specifically was to identify the distribution channel strategies adopted by commercial banks in Nigeria and to determine the effect of the distribution channel strategies adopted on the performance of the bank. The study adopted a descriptive survey research design. The population of the study was 43 management staff of five commercial banks operating in Nigeria. Questionnaire was used as the tool for data collection. The data was analyzed and presented using percentages, mean and standard deviation. The study found that the branch network, electronic banking and multiple distributions were used by the banks. Marketing strategies being employed by the banks were aggressive marketing, mass marketing and value marketing, the study further found that the adopted distribution channel strategies have a significant effect on the performance of the banks. It was recommended among other things that; commercial banks should adopt those marketing distribution strategies that ensure the performance of the bank is improved and do away with those which adds costs so that the banks can compete effectively with the others and that they should embrace the concept whole heartedly by adopting electronic banking as already the battle for the banks is technology usage which should be one which offers customers more features.